Barriers to immunization among children of migrant workers from Myanmar living in Tak province, Thailand. - Canavati, S; Plugge, E; Suwanjatuporn, S; Sombatrungjaroen, S; Nosten, F (2011)
PROBLEM: Immunization is a cost-effective means of improving child survival but implementation of programmes in low- and middle-income countries is variable. Children of migrants are less likely to be immunized. APPROACH: The qualitative study aimed to identify barriers to the successful implementation of migrant immunization programmes in Tak province, Thailand. We ran a total of 53 focus groups involving 371 participants in three sites. LOCAL SETTING: Tak province in Thailand borders Myanmar and has an estimated 200,000 migrants from Myanmar. Vaccine-preventable diseases are a documented cause of morbidity in this population but there is no systematic or coordinated immunization programme in the area. RELEVANT CHANGES: As a result of the findings, the subsequent immunization campaign targeted children in school to overcome those barriers of distance to immunization services, fear of arrest, not remembering immunization appointments, and the disruption of parental work. The campaigns also included immunization education for both parents and teachers. LESSONS LEARNT: Migrant parents identified similar barriers to accessing childhood immunization programmes as migrant populations elsewhere in the world, although a unique barrier identified by parents from Myanmar was "fear of arrest". The subsequent school-based strategy to overcome these barriers appears to be effective.